Superficial tension of metals and their some connections - Jurov, V.M.; Laurinas, V.Ch.; Guchenko, S.A.; Zavatskaja, O.N. (Recent Contributions to Physics, 2012)
In work new methods of definition of a superficial tension of solid states are described. At the heart of methods dimensional effects of physical properties of materials lay. The offered methods are used for definition of a superficial tension of pure metals and their some connections. Comparison of the offered methods with earlier known has shown their good conformity. However advantage of the offered methods are: a wide temperature range of measurements and the wide nomenclature of measured objects.
Keywords: surface tension of solids, size effects, nanocrystals